Modeling the Dark Triad of Personality (Machiavellianism, Psychopathy, and Narcissism) Based on Feelings of Inferiority, Anxiety, and Social Rejection with the Mediating Role of Impulse Control in Adolescents with a History of Running Away from Home - Ebadpoor, Aida; Nikooy, Maryam; mohammadkhani , Parvaneh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective:  This study aimed to model the Dark Triad of personality (Machiavellianism, psychopathy, and narcissism) based on feelings of inferiority, social anxiety, and social rejection with the mediating role of impulse control in adolescents with a history of running away from home.Methods and Materials: The research employed an applied and correlational design. The statistical population consisted of adolescents (girls and boys) aged 14–18 years attending drop-in harm reduction centers and night shelters in Tehran during the first half of 2023 (N = 2400). Using purposive sampling and Krejcie and Morgan’s table, 331 participants were selected. Data were collected through validated instruments, including the Short Dark Triad Questionnaire (SD3), the Feelings of Inferiority Questionnaire, the Liebowitz Social Anxiety Scale (LSAS-SR), the Social Isolation Questionnaire, and the Barratt Impulsiveness Scale (BIS-11). Structural equation modeling (SEM) was conducted using AMOS software to test the hypothesized model.Findings: Results demonstrated that feelings of inferiority (B = –0.42, β = –.36, p = .001), social anxiety (B = –0.39, β = –.31, p = .001), and social rejection (B = –0.34, β = –.28, p = .002) significantly predicted lower impulse control. In turn, impulse control significantly predicted Machiavellianism (B = –0.31, β = –.29, p = .001), psychopathy (B = –0.37, β = –.32, p = .001), and narcissism (B = –0.28, β = –.24, p = .003). Indirect effects confirmed mediation, for example, the effect of feelings of inferiority on Machiavellianism (β = –.11, p = .004). Model fit indices indicated acceptable fit (χ²/df = 2.23, CFI = .95, RMSEA = .062).Conclusion: Findings suggest that emotional vulnerabilities such as inferiority, anxiety, and rejection influence the development of Dark Triad traits primarily through impaired impulse control. These results emphasize the role of self-regulation as a protective factor and highlight the importance of preventive interventions targeting impulse control among vulnerable adolescents.